Menganalisis Strategi Pemasaran Indomie (PT Indofood Sukses Makmur Tbk) Dalam Pasar Internasional - Aurora Elise Putriku; Lenti Susanna Saragih; Novita Sari Br Siboro; Mutiara Dwi Rizqina; Michael Sihombing (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Abstract This research aims to analyze the marketing strategy of PT Indofood Sukses Makmur Tbk to enter the international market with a focus on Indomie instant noodle products. Obtain data from trusted sources such as academic journals and books through library research methods. A qualitative approach is used to understand Indomie's marketing strategy through content analysis and data interpretation. This company is famous for its high quality products and various innovations, especially in instant noodle products. Quality standardization in the production process is the key to success in the global market. Apart from that, PT Indofood Sukses Makmur Tbk applies the cost-plus method in determining export selling prices so that its products are flexible and competitive in the international market. In terms of distribution, the company attaches great importance to quality, timeliness, safety and transportation costs. Indomie products are distributed through large wholesalers and retailers and are popular in overseas markets such as Australia. The findings show that effective and efficient marketing strategies have helped PT Indofood Sukses Makmur Tbk maintain and expand its global market share.